IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DALAM MATA PELAJARAN BAHASA INDONESIA DI SEKOLAH MENENGAH PERTAMA 1 KENDAL KABUPATEN KENDAL - Achmad Fauzi; Titik Haryati; I Made Sudana (STKIP Subang, 2023)
The focus of this research is the Implementation of Differentiated Learning in Indonesian Language Subjects at State Junior High School 1 Kendal, Kendal Regency. The sub-focus of this research is: How to map the learning needs of students by using three aspects, namely learning readiness, interest and learning profile, the implementation of differentiated learning in accordance with the lesson plan that has been made, and the implementation of evaluation and reflection with the aim of being able to see the shortcomings and advantages as material for improving future learning in Indonesian language subjects in class VIII of State Junior High School 1 Kendal Kendal Regency? This research uses a descriptive qualitative method of case study type and the data collection method is carried out by interview, observation, and documentation techniques. The results of the research map the learning needs of students using three aspects, namely learning readiness, interest and learning profile, the implementation of differentiated learning in accordance with the lesson plan that has been made, and the implementation of evaluation and reflection with the aim of being able to see the shortcomings and strengths as material for improving future learning in Indonesian language subjects in class VIII State Junior High School 1 Kendal Kendal Regency, namely (1) differentiated learning based on learning readiness, interests and learning styles can be done in several ways, including: conducting diagnostic assessments before learning and analysing them, preparing lesson plans and devices based on learning readiness, interests, and learning styles of learners, implementing differentiated learning, and conducting evaluation, reflection and feedback, (2) effective teaching strategies are general patterns of teacher and learner activities in the realisation of learning activities to achieve competence as learning objectives optimally. Usually, to determine effective teaching strategies, teachers need to understand the characteristics of learners and choose strategies that suit their needs, and (3) evaluation and self-reflection are reports carried out by various activities such as classroom observation, giving questionnaires to learners about the implementation of learning and the results of evaluation and reflection are discussed with peers facilitated by schools for continuous work improvement involved in improving the quality of learning and the achievement of learner learning outcomes. The conclusion of this research is (1) differentiated learning that teachers must map the learning needs of students who are very complex. For this reason, teachers must have independent, reflective, collaborative, innovative, and learner-centred values as capital in implementing learner-centred learning, (2) the implementation of differentiated learning in accordance with the lesson plan that has been made in Indonesian language subjects is to explain learning outcomes, learning objectives, and the flow of learning objectives to be achieved, and (3) evaluation and reflection with the aim of being able to see the shortcomings and strengths as material for improving future learning in Indonesian language subjects is the implementation of an independent curriculum in schools, making teachers apply learning with a new paradigm.